The Beatles: ensaio sobre a ética do amor - Anjos, Francisco Flávio Oliveira dos (2007)
The thesis intends to discuss the ethics by the way of love. So, it uses as a mention the musical work and the set of attitudes of the group that changed the way of thinking across the 20th Century mass-comm, entering a new way of thinking about the World: The Beatles. Analyzing the lyrics and the writing of the songs was searched the comprehension of he intrinsic love message at the Ethics it expresses. At the musical art of The Beatles political messages had been announced in a time that the World sought a Ethic way beyond the several declared war and the Cold War. Taking the Edgar Morin works as a base, O método 6, Ética (2005), it sought to understand the idea who permeates the human relations: the good, the possible, the necessary. Another works used as a cognitive base were Meus demônios (2003), Cultura de massas no Século XX: neurose (2005), Cultura de massas no Século XX (2006), The Beatles Anthology (2000) and Many years from now (2000). Holding the Ethics idea showed by Morin were established imaginary lines that perpass the behavior of the group known in the entire World understood till nowadays as tolerance, comprehension, peace, love and endurance messengers. The Beatles operate during the sixties a musical reborn, which allowed to the people the discussion and the reflexion about the World and the human being new behavior,endurance but acting with tolerance. Permeating the basic study, we find the Beatles way, the group origin, the fast walk till success, the spiritual choice, who guide their behavior and the end of the band. The music used as a masscomp instrument passes by the condition of a simple way of communicating. It deeply action feeds feelings, allows transcendence and is showed as target of human being transformation. The Ethics in music passes by the ideological barriers and becomes to comprehension with a clear synthony for the man, cause the polyphony and the new musical order establish the messages worldwide